Efektivitas Penerapan Surat Edaran Mahkamah Agung No. 1 Tahun 2023 Tentang Pelaksanaan Panggilan dan Pemberitahuan Melalui Surat Tercatat: Studi Pengadilan Agama Donggala - Syukri, Muhammad; Yamani, Gasim; Raden, Sahran; Sabubu, Theo Alif Wahyu (Jurnal Ragam Pengabdian, 2026)
This study examines the effectiveness and the supporting or inhibiting factors of Supreme Court Circular Letter (SEMA) No. 1 of 2023 regarding summons via registered mail at the Donggala Religious Court Class IB. This empirical juridical research uses a qualitative descriptive design. Data were gathered through observation, documentation, and interviews with judges, registrars, advocates, and litigants. The results show that the normative standing of SEMA No. 1 of 2023 is effective as an internally binding policy. It successfully accelerates case management, reduces court costs, and increases administrative transparency through digital tracking. Supporting factors include explicit administrative guidelines, cost efficiency, and robust institutional cooperation with the postal service. Inhibiting factors consist of inaccurate party addresses, geographical obstacles, and low digital or administrative literacy among the rural public. Overall, this policy successfully modernizes judicial administration, though continuous technical coordination and broader public socialization remain essential to maintain procedural justice.